2021
DOI: 10.1017/s1047951121003954
|View full text |Cite
|
Sign up to set email alerts
|

Late outcome, therapy and systemic ventricular function in patients with a systemic right ventricle: data of the German National Register for Congenital Heart Defects

Abstract: Background: Adults with systemic right ventricle have a significant risk for long-term complications such as arrhythmias or heart failure. Methods: A nationwide retrospective study based on the German National Register for Congenital Heart Disease was performed. Patients with transposition of the great arteries after atrial switch operation or congenitally corrected TGA were included. Results: Two hundred and eight-five patients with transposition of the great arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Moreover, recent studies revealed a correlation of left ventricular outflow tract obstruction (LVOTO) with sRV function, suggesting a positive effect of the LVOTO on hemodynamic status and thus a potential protective effect on sRV systolic in the long-term [ 52 , 53 ].…”
Section: Heart Failure (Hf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies revealed a correlation of left ventricular outflow tract obstruction (LVOTO) with sRV function, suggesting a positive effect of the LVOTO on hemodynamic status and thus a potential protective effect on sRV systolic in the long-term [ 52 , 53 ].…”
Section: Heart Failure (Hf)mentioning
confidence: 99%
“…Primary ventricular tachycardia occurs in about 20% of the patients with ccTGA, especially in those with sRVd [ 53 , 126 ]. This prevalence, which is higher compared to patients after AtSO, may be explained by multiple substrates for dysrhythmia ventricular scars in patients undergoing a physiologic repair strategy (such as the presence of or a possible association with accessory pathways in patients with Ebstein-like valve).…”
Section: Sudden Cardiac Death (Scd)mentioning
confidence: 99%
See 1 more Smart Citation
“…These surgical operations underwent several modifications in the last six decades. Patients with TGA, who still have RV in a systemic position are known to be at risk for heart failure (HF), atrial and ventricular arrhythmia, and sudden death ( 3 , 4 ). The occurrence of overt HF has negative implications on the prognosis of CHD patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a systemic right ventricle (SRV) represent a significant proportion of adults with congenital heart defects (CHD) [1]. Over time, most of them show various degrees of heart failure (HF) symptoms [1][2][3][4][5]. The lack of clear guidelines based on hard evidence and the increasing number of adult CHD patients make treatment of SRV failure one of today's greatest challenges.…”
mentioning
confidence: 99%